A Multicenter Hospital Surveillance of Invasive Streptococcus pneumoniae, Puerto Rico, 2001 - Rivera-Matos, Idalia R.; Rios-Olivares, Eddy (Puerto Rico Health Sciences Journal, 2005)
Although antimicrobial resistance to Streptococcus pneumoniae has been increased dramatically worldwide, there is limited information of pattern of susceptibility for this pathogen in Puerto Rico. Hospitalbased surveillance for invasive pneumococcal infections was begun among 38 hospitals island-wide in Puerto Rico from January to December, 2001. One hundred ninety-two cases of invasive pneumococcal disease were identified. Of the 177 isolates available for susceptibility testing, 50.3% were susceptible to penicillin and 49.7% were nonsusceptible (intermediate (I) and resistance (R)) (19.2% I , 30.5% R). Resistance was documented for expanded spectrum cephalosporins and macrolides. All isolates were susceptible to vancomycin. Diabetes, cardiovascular disease, smoking and bronchial asthma were the most common risk factors associated with invasive pneumococcal disease of the adult population. Bronchial asthma was the most common disease in the pediatric population with a fatality rate of 21%. There was no increased mortality detected among patients infected with penicillin resistant strains. Most of the isolates serotypes are represented in the 23-valent polysaccharide vaccine (78%) and 7-valent conjugate vaccine (62%). Penicillin-resistant isolates (47%) were 14, 19F, 6B, 6A, 9V, 23F, 19A and 35B serotype. Our data indicated a high prevalence for drug-resistant strains of S. pneumoniae in Puerto Rico. Continue surveillance for this common but serious pathogen is needed. Asthma is an important risk factor for pneumococcal disease. The pneumococcal vaccine should be recommended for all age groups with this risk factor.